MUSLIM IDENTITY AND DEMOCRATIC SOCIALISM: READING ZOHRAN MAMDANI'S MAYORAL VICTORY IN NEW YORK CITY - Pulungan, Eska Dwipayana (Jurnal Al-Ijtimaiyyah, 2026)
This study analyzes Zohran Mamdani's victory in the 2025 New York City mayoral election, a result widely regarded as a triumph for the city's pluralistic society given Mamdani's identity as a Muslim and a member of a minority group. Throughout the campaign, Mamdani faced sustained attacks from political opponents, both Republicans and fellow Democrats, who targeted his Muslim identity directly. This study employs a qualitative method, drawing on books and journal articles to examine the foundations of socialist thought, supplemented by international news coverage to trace Mamdani's campaign strategy. The findings show that Mamdani was elected as the 111th mayor of New York with 50.4% of the vote, far surpassing Andrew Cuomo and Curtis Sliwa. This outcome indicates strong public trust in a democratic socialist platform centered on prosperity, including reduced housing costs and lower prices for basic necessities. For non-Muslim voters, Mamdani's religious identity was not perceived as an obstacle to leadership; rather, identity politics was seen merely as a tactic used by opponents to influence the election. For Muslim voters, rising costs of living, transportation difficulties, and housing rents were understood as collective burdens rather than the responsibility of any single group—an outlook aligned with both democratic socialist principles and Islamic values. These findings suggest that Mamdani's faith bears no relation to any erosion of democratic values, contrary to claims made by his political rivals. Ultimately, Mamdani's victory demonstrates his capacity to position New York City as an inclusive city, particularly for its lower-middle-class population.